Theoretical Intakes of Modern-Day Paleo Diets: Comparison to U.S. Dietary Reference Intakes. (7th June 2021) - Karlsen, Micaela; Livingston, Kara; Agoulnik, Dasha; Miki, Akari; Lichtenstein, Alice; Folta, Sara; Economos, Christina; Gilhooly, Cheryl; Jacques, Paul; McKeown, Nicola
Abstract: Objectives: To evaluate the nutrient adequacy of theoretical, modern-day Paleo meal plans relative to the U.S. Dietary Reference Intakes (DRIs). Methods: This analysis used data from the Adhering to Dietary Approaches for Personal Taste (ADAPT) Feasibility Study, which captured data on 9 726 self-reported, popular diet followers. Paleo respondents (N = 925) reported sources of recipes and diet guidance. Five days from each of the top six sources were used to generate 30 days of meal plans among a random sample of n  = 200 Paleo respondents. Nutrition Data System for Research (NDSR) was used to estimate daily nutrient content of meal plans which was compared to DRIs and recommendations, as follows: recommended daily allowances (RDAs) for vitamins D, E, and folate, which do not vary by age (years, y)/sex; sex and age-specific RDAs for vitamins A, C, calcium (Ca), magnesium (Mg), and iron (Fe); adequate intakes (AIs) for potassium (K) and fiber; upper intake level (UL) for sodium (Na); and Dietary Guidelines for Americans (DGA) upper threshold to limit saturated fat and Na. Results: Estimated daily nutrient intakes of theoretical Paleo meal plans met or exceeded RDAs for the following (Paleo vs. RDA): vitamin A for men or women (1481 RAE µg vs. 900 μg and 700 µg), vitamin D (56 µg vs. 15 μg), vitamin E (27 mg vs. 15 mg), folate (489 µg vs. 400 μg), vitamin C for men or women (225 mg vs. 90 mg and 75 mg), Mg for men and women 31–70 y (539 mg vs. 420 mg and 320 mg), and Fe for men (16 mg vs. 8 mg). Theoretical estimates did not meet the following: RDAs for carbohydrate (91 g vs. 130 g), Fe for women 19–50 y (16 g vs.18 mg), Ca for men and women 61–70 y (562 mg vs. 1000 mg and 1200 mg), and AI for K (4027 mg vs. 4700 mg) or dietary fiber (25 g vs. 28 g/2000 kcal). Estimated levels of Na exceeded the UL (2763 mg vs. 2300 mg), saturated fat exceeded the DGA (19% vs. 10% kcal), and added sugar levels fell within the recommendation (1% vs. 10%). Conclusions: While certain aspects of the Paleo diet offer improvements over typical reported intakes of US adults, saturated fat is high, and carbohydrate, fiber, Ca, and K levels of these theoretical diets do not meet DRIs. High levels of saturated fat present concern for cardiovascular health. Optimal nutrition may be challenging to sustain on a Paleo diet. Funding Sources: Supported by USDA Cooperative Agreements 58-8050-9-004 and 58-8050-9-003.